The Real Exchange Rate and External Competitiveness in Egypt, Morocco and Tunisia - Zuzana Brixiova; Balázs Égert; Thouraya Hadj Amor Essid (Institute for the Study of Labor (IZA), 2013)
Egypt, Morocco and Tunisia face challenges competing on the global markets, as shown by their relatively low and stagnant export shares. The limited export competitiveness has hampered external demand, growth and employment. Applying, for the first time to North Africa, the stock-flow approach to the real equilibrium exchange rate, this paper evaluates the countries' real exchange rate misalignments during the past three decades. While Egypt experienced periods of substantial misalignment, including in recent years, the exchange rates in Morocco and Tunisia have broadly reflected the underlying fundamentals. In all three countries structural factors are key to boosting exports, alongside of avoiding sizeable future misalignments. Intra-regional trade both with North Africa and the rest of the continent together with greater orientation to fast growing emerging markets could also raise countries' external competitiveness.
Keywords: F3; F41; F63; C5; O1; 330; real exchange rate misalignment; stock-flow model; competitiveness; trade; employment; North Africa